Program Kotaku dalam Perspektif Pendidikan Islam - Imas Widiyanti (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2021)
Abstrak Conceptually, the government's effort in slum settlements is the realization of the Kotaku program The Kotaku program is implemented nationally in 269 cities / districts in 34 provinces. This is done through activities in slum areas that are channeled through infrastructure development activities as well as social and economic assistance for the sustainability of communities in slum settlements. My city program is implemented for structuring slum areas in Kricak Tegalrejo Village, Yogyakarta. The methodology is carried out by interviewing, observing and documenting several local governments and civil society. Community-based education is a model for delivering education based on the principles of society, by the community and for the community. In Islamic education, it is also management to teach awareness from an early age about environmental cleanliness so that through the Kotaku program which has the aim of building systems, facilities, and communities. This research uses descriptive qualitative research methods that are thorough, in-depth, and careful.